Public Service Innovation Deficiency: The Case of Quick Wins Program (Online Driving License) in East Java Police Department - Wijaya, Andy F. (International Journal of Psychosocial Rehabilitation, 2020)
Scholars argue that public service innovation constantly makes a positive contribution to the citizen. That being said, the appropriate innovation management by the public sector is still arguable. Metaphorically, public service innovation is a black box; its implementation in the daily operation of the organization remains unclear. Therefore, this research uncovers the reality in which a specific organization implements the innovative program; we conducted a study on innovations in the police department and analyzed the imperfect implementation of the innovative program. This research works with the organization's complexity since the police department is exploring ways to improve their service; also, the police department has organizational red-tapes such as overlapping rules and regulations, as well as its semi-militaristic organization type. Researchers employed a qualitative approach to uncover the problem and constructed the evident implementation in the organization’s daily operation. The study revealed three inhibitors: external, internal and political inhibitors; the internal inhibitors were obtained from human resources competency and socialization issues, the external inhibitors were obtained from technological systems and users, and the political inhibitors consisted of budget and availability of funding sources.